Antimicrobial Susceptibility Pattern of Staphylococcus aureus Isolated from PNS Shifa Hospital, Karachi, Pakistan - Nadeem, Saman; Hanif, Faisal; Taj, Yasmeen; Hussain, Beenish; Zehra, Nadia Midhat (Infectious Diseases Journal of Pakistan, 2023)
Objective: To determine antimicrobial susceptibility pattern of Staphylococcus aureus in a tertiary care hospital, Karachi. Study design Descriptive cross sectional. Place and Duration of study: The study was carried out in Department of Microbiology, PNS Shifa hospital, Karachi from June 2014 to May 2016. Materials and Methods: A total of 2240 samples are selected for the study among which 1132 samples revealed the growth of different microorganisms. Samples of pus, blood, body fluids, and sputum and wound swabs are included and different biochemical reactions are performed in order to identify Staphylococcus aureus isolates. The antimicrobial susceptibility of these isolates are performed by disk diffusion method using cefoxitin (30μg) and different antibiotics are tested against methicillin resistant and sensitive staphylococcus isolates as outlined by Clinical Laboratory Standard International Guidelines. Results: Among different samples, total 592 samples showed the growth of Staphylococcus aureus. Among them n=377 (64%) isolates were methicillin resistant Staphylococcus aureus, and n=215 isolates were methicillin sensitive (36%). Out of 377 isolates of methicillin resistant staphylococcus aureus (MRSA) from different clinical samples, 79% (n=298) isolates are from pus samples. We have also isolated 215 MSSA, 82% (n=176) are isolated from pus. Out of 377 isolates of MRSA, 41% (n=153) are susceptible to tigecycline, 15% (n=57) susceptible to erythromycin, 46% (n=172) sensitive to clindamycin, 28% (n=106) sensitive to cotrimoxazole, 66% (n=250) sensitive to doxycycline, 72% (n=272) sensitive to chloramphenicol, and 17% (n=65) sensitive to ciprofloxacin. Among 215 isolates of staphylococcus aureus (methicillin sensitive), 50% (n=108) of isolates were sensitive to tigecycline, 41% (n=88) were sensitive to erythromycin, 55% (n=118) were sensitive to clindamycin, 53% (n=113) were sensitive to cotrimoxazole, 74% (n=160) were sensitive to doxycycline, 71% (n=152) were sensitive to chloramphenicol, 58% (n=125) were sensitive to ciprofloxacin. All strains of Staphylococcus aureus (methicillin resistant and sensitive) are found susceptible to vancomycin and linezolid, 100% (n=592). Conclusion: The antibiotic susceptibility pattern obtained from the above study showed a lot of antimicrobial choices available for staphylococcus aureus, so the use of Vancomycin and linezolid should be the last resort for treating such infections. It also draws attention towards increasing resistance among the widely used antibiotic such as ciprofloxacin so its overuse should be discouraged. Key words: Antimicrobial susceptibility, Methicillin resistant Staphylococcus aureus, Staphylococcus aureus